Symptom prevalence and risk factors for asthma at the rural regions of Denizli, Turkey - Uğurlu, Erhan; Öncel, Sevin Başer; Evyapan, Fatma (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
Objective: This study was conducted using a standardised method (ECRHS) to identify the prevalence of asthma symptoms and risk factors in adults who lives in the rural regions of Denizli province. Methods: This study was designed as a cross-sectional study to investigate the prevalence of asthma and asthma symptoms in adults older than 18 years old, around the rural regions of Denizli. Data were collected by personal interview and filling in questionnaires between July 2009 and September 2009. Results: A total of 1,343 individuals were enrolled. Prevalence of current asthma was 5.9%, having an asthma-like symptom was 34.0% and allergic rhinitis was 2.5%. Most common asthma symptoms were woken by an attack of breathlessness (20.5%, n=275), woken by attack of cough (19.9%, n=267) and wheezing (12.7%, n=171). Conclusions: Asthma is an important disease that may occur not only in cities but also at country sides. In rural areas risk factors for asthma and asthma-like symptoms compared to urban areas may show some differences.